Clinical Evaluation of Direct Composite Resin Restorations in Fractured Anterior Teeth - Ramírez Barrantes DDS, MS, PhD, Juan Carlos; Araujo Jr DDS, MS, PhD, Edson; Narciso Baratieri DDS, MS, PhD, Luiz (Odovtos - International Journal of Dental Sciences, 2015)
he aim of this In Vivo study was to evaluate the influence of the cavosurface angle (with bevel, and no preparation), of direct composite resin restorations in previous fractured teeth after 4 years of clinical performance. The restorations were performed by a single operator, following a restorative standardized protocol. For the study were selected 24 upper central incisors with fracture or with class IV restorations with an indication of replacement. According to the restorative technique, the teeth were divided into 2 groups: group I (n = 12) Class IV Restorations with a bevel preparation technique; and group II (n = 12) Class IV Restorations performed with no preparation. The restorations were evaluated at 7 days and 4 years, by two examiners, previously calibrated using modified USPHS criteria. After 4 years, two restorations were excluded, representing 22 restorations (11 with bevel preparation, and 11 without). The Fisher test demonstrates no significant differences between groups (p > 0.05). This study presents clinical evidence that the cavosurface angle configuration does not influence the clinical performance of direct composite resin restorations in fractured teeth. Thus, we recommend no preparation of the cavosurface angle to preserve sound dental tissue based on a Minimally Invasive Dentistry approach.